2014
DOI: 10.1614/ws-d-13-00116.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Emergence of 23 Summer Annual Weed Species

Abstract: First- and second-year seedbank emergence of 23 summer annual weed species common to U.S. corn production systems was studied. Field experiments were conducted between 1996 and 1999 at the Iowa State University Johnson Farm in Story County, Iowa. In the fall of 1996 and again in 1997, 1,000 seeds for most species were planted in plastic crates. Seedling emergence was counted weekly for a 2-yr period following seed burial (starting in early spring). Soil temperature at 2 cm depth was estimated using soil temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
124
2
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(150 citation statements)
references
References 44 publications
9
124
2
15
Order By: Relevance
“…This awareness induced increasing interest in the development of models that can simulate seedling emergence and the potential benefits, but also challenges, of their adoption were recognised and thoroughly reviewed (Forcella et al 2000;Grundy 2003). Several models have been created for seedling emergence of various weed species in the main crops such as maize (Dorado et al 2009a;Masin et al 2012), soybean Werle et al 2014) or winter cereals (Royo-Esnal et al 2010, 2015García et al 2013;Izquierdo et al 2013). These models are often based on the hydrothermal time concept (Bradford 2002) and require the estimation of biological parameters, base temperature, and base water potential for germination (t b and Y b hereinafter), to simulate seedling emergence according to weather trends.…”
mentioning
confidence: 99%
“…This awareness induced increasing interest in the development of models that can simulate seedling emergence and the potential benefits, but also challenges, of their adoption were recognised and thoroughly reviewed (Forcella et al 2000;Grundy 2003). Several models have been created for seedling emergence of various weed species in the main crops such as maize (Dorado et al 2009a;Masin et al 2012), soybean Werle et al 2014) or winter cereals (Royo-Esnal et al 2010, 2015García et al 2013;Izquierdo et al 2013). These models are often based on the hydrothermal time concept (Bradford 2002) and require the estimation of biological parameters, base temperature, and base water potential for germination (t b and Y b hereinafter), to simulate seedling emergence according to weather trends.…”
mentioning
confidence: 99%
“…Akaike weights (w i ) closer to 1 indicate stronger support for a candidate model given the data. This methodology has been used in previous giant ragweed emergence modeling studies to select the best-fitting predictive model while minimizing the number of parameters (Davis et al 2013;Werle et al 2014). Since AICc will rank models even if none perform well, it is recommended that additional performance criteria be used (Anderson 2008;Kobayashi and Salam 2000;Legates and McCabe 1999;Meek et al 2009;Tedeschi 2006).…”
Section: Methodsmentioning
confidence: 99%
“…All other published models use the Weibull function to predict giant ragweed emergence. The models from Schutte et al (2008) and Werle et al (2014) include only fixed effects:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Widespread resistance in common waterhemp against ALS-inhibiting herbicides and glyphosate is compelling soybean growers to depend mostly on PPO-inhibiting herbicides such as acifluorfen, fomesafen, or lactofen (Shoup et al 2003;Shoup and Al-Khatib 2004). Hartzler et al (1999) reported that common waterhemp has an extended period of emergence compared to other summer annual weed species, and Werle et al (2014) considered this weed as a late-emerging species. The PRE (soil-applied) herbicides may lose their residual activity later in the growing season; therefore, the application of POST herbicide is necessary to control late-emerging common waterhemp flushes (Hager et al 2002a).…”
mentioning
confidence: 99%